Indentation of rigid rough surface into polymer coating layer - Ogar, Petr; Kozhevnikov, Artem; Elsukov, Vladimir (International Journal of Engineering and Technology, 2018)
An analysis of engineering approaches to determining the value of the introduction of spherical asperity and a rough surface into the polymer layer is given. It is shown that engineering methods of solving contact problems on the basis of simplifying hypotheses are more practical, for example, the representation of a layered body as a construction with special mechanical properties that depend on the mechanical properties of base and coating materials and the thickness of the coating. Analysis of the use of the proposed engineering solutions in calculating the value of the indentation of the sphere showed the advantages of the method based on the rigid model of a layered body. In this case, the effective modulus of elasticity and the Poisson's ratio are determined for any values of the coating thickness for an axisymmetric loading of a layered half-space. To determine the value of the indentation of a rough surface into the polymer layer, a discrete model of a rough surface is used. When contacting a rough surface through a polymer layer, it was taken into account that each asperity corresponds to a certain modulus of elasticity, which is determined by the level of the peak and the value of approach.Â Â